Simulation study on water yield service flow based on the InVEST-Geoda-Gephi network: A case study on Wuyi Mountains, China - Chen, Xin; Lin, Shiyu; Tian, Jie; Wang, Yujie; Ye, Yongxiang; Dong, Sining; Gong, Xiaoling; Lin, Qinlan; Zhu, Liying (Ecological indicators, 2024)
•A methodology was constructed to study the dynamics of water yield service flows at multiple scales.•Reveal the vulnerability of ecosystem service potential conflicts by analyzing and assessing the interactions between supply and demand.•We use network models to analyze ecosystem service flow processes and visualize supply flow trajectories in mountain ecosystems.•The "InVEST-Geoda-Gephi" method has practical applications for ecological conservation and management decision-making in mountain ecosystems. In an era marked by escalating demand for water resources and expanding human encroachment, numerous regions worldwide find it very challenging to balance water supply and demand. As a key source of water yield services, ecosystems often fail to spatially satisfy the great demand for water resources in some areas. This study focuses on the role of ecosystems in the supply and demand of water yield services in human social systems and then maps the flow between them. It quantifies their intricate relationship by employing the concept of ecosystem service flow. A notable gap exists in methodologies that intuitively illustrates the 'supply-movement-demand' dynamics in this context. Consequently, this study introduces a comprehensive methodology by integrating multiple models such as 'InVEST-Geoda-Gephi' to investigate the transmission paths and characteristics of surplus and deficit distribution of water yield service flow across various scales. Firstly, the spatiotemporal evolution of water yield service supply and demand within ecosystems is analyzed. Secondly, we scrutinize regional supply and demand alignment spatial patterns utilizing the Geoda model. Subsequently, the Gephi network model simulates water yield service flow from ecosystems to human social systems. The findings corroborate the network model's effectiveness and visual capabilities in representing ecosystem service flow across diverse scales. The primary conclusions drawn are as follows: (a) The spatiotemporal distribution of water yield services around the Wuyi Mountains exhibited a pattern characterized as 'high in the center, low on the edges' from 2000 to 2020, revealing significant spatial heterogeneity between high-supply and high-demand areas; (b) Influenced by the mountainous region's supply, the study area was mainly characterized by a high-low spatial mismatch. High-high spatial match was mainly distributed in provincial capitals and selected coastal economic zones. In contrast, low-low spatial match transitioned from northwest to southwest, and low–high mismatch encircled in areas featuring both high supply and high demand, particularly around provincial capitals and adjacent undeveloped coastal regions; (c) With the advance of urbanization and economic development, deficit nodes in the water yield service flow network tended to be marginalized, which reduced network density and connectivity leading to a decline in the ability of Wuyi Mountains ecosystem to provide water yield services and weakening its flow to human social systems due to external interference. This research provides strategic guidance for rationally allocating water resources in regional ecosystems and promoting ecological protection and collaborative development.